ANALISIS KEGIATAN PROJEK PENGUATAN PROFIL PELAJAR PANCASILA (P5) PADA KURIKULUM MERDEKA DI KELAS IV SD NEGERI 9 RANTAU PANJANG - Lisma Khoirunnisak; Treny Hera; Tanzimah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The study aims to analyze the activities of the Pancasila student profile strengthening project in the independent curriculum in class IV of SD Negeri 9 Rantau Panjang. This study is a qualitative study with a case study approach with descriptive data types. The focus of this study is on P5 activities in the independent curriculum of class IV of SD Negeri 9 Rantau Panjang and the sub-focus of this study is how to utilize P5 through collaboration between students in completing the ecobrick project. The data collection techniques used are observation, interviews and documentation. The previous P5 results were market day then the researcher continued by making ecobricks. In making ecobricks, measuring creative students. Based on the results of observations that the criteria for student creativity in P5 activities are very good.